Copper oxide supported on three-dimensional ammonia-doped porous reduced graphene oxide prepared through electrophoretic deposition for non-enzymatic glucose sensing - Maaoui, H.; Singh, S. K.; Teodorescu, F.; Coffinier, Y.; Barras, A.; Chtourou, R.; Kurungot, S.; Szunerits, S.; Boukherroub, R. (Electrochimica Acta, 2017)
The paper reports on the preparation of N-doped porous reduced graphene oxide/copper oxide (ammonia-doped-prGO/CuO) nanocomposite on gold electrodes using electrophoretic deposition (EPD) from an ethanolic suspension of ammonia-doped-prGO and Cu(ClO4)(2) by applying a DC voltage. The ammonia-doped-prGO/CuO nanocomposite film thickness is controlled by varying the deposition time. Morphological analysis using scanning electron microscopy (SEM) showed the formation of a 3 dimensional structure with CuO nanoparticles being homogeneously embedded in the graphene layer. Xray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Raman analysis revealed that the deposited copper was in its oxidized form, mainly CuO. The Au/ammonia-doped-prGO/CuO electrode was successfully applied for non-enzymatic amperometric detection of glucose. Under optimized conditions, the electrode exhibited a sensitivity of 1210 mu mM(-1) cm(-2) with a detection limit of 0.25 p,M (S/N =3) over a wide concentration range (0.25 mu M to 6 mM) at an applied potential of +0.50 V vs. Ag/AgCl. The electrode material displayed good stability, excellent selectivity, and accurate measurement in healthy and diabetic human serum samples.

N-doped porous reduced graphene oxide as an efficient electrode material for high performance flexible solid-state supercapacitor - Singh, S. K.; Dhavale, V. M.; Boukherroub, R.; Kurungot, S.; Szunerits, S. (Applied Materials Today, 2017)
Supercapacitors (SCs) are energy storage devices with an immense potential to resolve energy related issues. Being a low cost, durable and multifunctional material, graphene and its derivatives are the most promising candidates for SCs. Here, we report the synthesis of N-doped porous reduced graphene (N-pGr) and its use for the fabrication of all-solid-state supercapacitor (ASSC) device. The N-pGr exhibited a specific capacitance of 230 F g(-1) at 1 A g(-1) current density and good capacitance retention up to 88% even after 10,000 galvanostatic charge-discharge cycles recorded at 5 A g(-1) fabricated in a solid-state supercapacitor. The synergistic effect of the porosity and N-doping is believed to be the underlying principle for the improved charge storage ability when compared to other reports. Significantly, the porous nature of N-pGr contributes in increasing the electroactive surface area for the formation of electrical double layer as well as facilitating the faster movement of electrolyte ions inside the electrode network. N-doping is believed to change the electrical properties of the electrode material and also to participate in the pseudo-capacitance which helped to boost the overall capacitance of the fabricated device. The good capacitance retention provides the room for making robust flexible solid-state supercapacitor (FSSC) with the N-pGr material.